I am number four : the lost files : secret histories - Lore, Pittacus (New York : Harper, 2013)
The second collection of action-packed novellas from Pittacus Lore. Initially published separately as digital originals, these three stories are now together in one print volume.
The forgotten ones
Companion to: The Lorien legacies.
Keywords: Extraterrestrial beings -- Fiction; Science fiction